2011
DOI: 10.1103/physrevd.84.125014
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of a planar nonbirefringent andCPT-even electrodynamics stemming from the standard model extension

Abstract: We have studied a (1+2)-dimensional Lorentz-violating model which is obtained from the dimensional reduction of the nonbirefringent sector of the CPT-even electrodynamics of the standard model extension (SME). The planar theory contains a gauge sector and a scalar sector which are linearly coupled by means of a Lorentz-invariance violating (LIV) vector, S µ , while the kinetic terms of both sectors are affected by the components of a Lorentz-violating symmetric tensor, κ µν . The energy-momentum tensor reveals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…Therefore, the natural question is whether the ambiguity can emerge for the CPT-even terms, those ones proportional to a constant evenrank tensor. Recently, the four-dimensional aether-like term in the nonmimimal QED, with a magnetic coupling only, was discussed and shown to be ambiguous [17,18] (a number of issues related to this term has been discussed in [19][20][21][22][23][24][25][26]). Further, in [27] it was shown that the ambiguity vanishes in a purely nonminimal sector, if we consider a gauge theory involving both minimal and nonminimal couplings, and impose a gauge-preserving regularization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the natural question is whether the ambiguity can emerge for the CPT-even terms, those ones proportional to a constant evenrank tensor. Recently, the four-dimensional aether-like term in the nonmimimal QED, with a magnetic coupling only, was discussed and shown to be ambiguous [17,18] (a number of issues related to this term has been discussed in [19][20][21][22][23][24][25][26]). Further, in [27] it was shown that the ambiguity vanishes in a purely nonminimal sector, if we consider a gauge theory involving both minimal and nonminimal couplings, and impose a gauge-preserving regularization.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [42,43] investigated the Lorentz violation theory of Dirac equation in flat Euclidean space using ether like vectors u α . Many interesting results of Hawking radiation of black hole with Lorentz violation theory have also been discussed in [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Many examples of Lorentz-breaking extensions of well-known models are presented in [1]. These theories are known to display nontrivial features both at classical [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (birefringence of electromagnetic waves in the vacuum, superluminal modes of propagation, non-zero magnetic moment for neutral elementary particles, etc.) and quantum levels.…”
Section: Introductionmentioning
confidence: 99%